A multi-laser sensor system to measure rolling deformation for truck tyres. Issue 2 (2017) - Xiong, Yi; Tuononen, Ari
The rolling deformation of a tyre is a direct result of tyre-road interactions and therefore contains useful information for tyre design. This study proposes a multi-laser sensor system for rolling tyre deformation measurements and the methodology is illustrated in detail. On-board validation tests were conducted with a truck tyre under service conditions. Tyre inner contour changes due to the inflation and wheel load were measured. In addition, non-uniform tread deformations were observed within the contact patch. In the longitudinal direction, asymmetric tread deformations which have direct links to rolling resistance were observed, while, in the lateral direction, the tread deformation pattern were found related to the inflation pressure and wheel load. The preliminary measurement results demonstrate the feasibility of the proposed system as a tool for investigations on tyre-road interactions and validations of virtual tyre models.